Evaluation of Antioxidant Activity and Optimization of Cookie Shelf Life Prediction with Durian Peel Flour Substitution - Anita Rahmiwati; Fitria Febriani (AgriHealth: Journal of Agri-food, Nutrition and Public Health, 2025)
Antioxidants are essential elements in scavenging free radicals and are found in many foods. Incorporating fiber-rich durian inner skin flour into cookies not only boosts the fiber content but also introduces antioxidant compounds, which may influence the product’s shelf life due to changes in chemical stability. Therefore, this study aimed to determine the antioxidant activity and shelf life of cookies. A randomized block design was adopted, and antioxidants were analyzed using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) method. The shelf life was estimated using the Accelerated Shelf-Life Testing (ASLT) method with the Arrhenius model during a 28-day storage period based on moisture content. The results showed that the antioxidant activity of cookies substituted with durian peel flour had IC50 values of 36.59 and 36.71 ppm, respectively, indicating a very strong antioxidant effect (IC50 < 50 ppm). Furthermore, the shelf life decreased with increasing storage temperature, namely, 26 days at 25 °C, 24 days at 35 °C, and 21 days at 45 °C. In conclusion, the substitution of durian peel flour increased antioxidant activity without significantly affecting shelf life.